Abandoned housing projects in Malaysia: a building law perspective - Md Dahlan, Nuarrual Hilal (2021)
Housing programme has been robustly implemented in Malaysia since Independence. At the commencement of the programme, the Federal Government provided housing accommodation to its citizens. However, due to the high demand for housing and the inability of the Government, the Government invited private sector to cooperate in supplying housing. Several laws have been enacted to control the housing industry. Among the laws are the Street, Drainage and Building Act 1974 (Act 133)('SDBA') and the Uniform Building By-Laws 1984 (G.N.5178/1984) ('UBBL'). Despite there are various housing policies and legislations to support housing programme, there are still many problems arising from the housing programmes in Malaysia. An example of the problems is the abandoned housing projects. Since the 1970s until todate, this issue is still occurring in Malaysia. Many purchasers have become aggrieved, suffered damage and losses. This paper aims to highlight the problems of abandoned housing projects through the analysis of building laws in Malaysia. This paper used qualitative case study and legal research methodologies to analyse the issues and to meet the research objectives. Through this paper, it is evident that there are weaknesses in the building laws. Hence, appropriate amendments and improvements to the laws should be made to empower the laws and provide adequate measures against the issues. The results of this paper will provide new ideas to housing practitioners and policymakers in dealing with the problems of abandoned housing projects in Malaysia towards achieving the 11th Malaysia Plan and Housing Policy (2018-2025)(‘DPN’).